Where to Look for Information When Planning Scientific Research in Psychology: Sources and Channels - Livacic-Rojas, P (2014)
It is imperative that researchers invest time in the planning of their research, and it is certainly essential to stop and seek information before making any kind of decision. The present work sets out to guide psychologists in this crucial task. To this end we begin by suggesting a visit to the APA website, where a great deal of relevant information on most topics can be found, whether it pertains to new and controversial issues or to those on which there is greater consensus. In this regard we shall consider at length the meanings of the expressions "evidence-based practice" and "scientific evidence" and their inherent methodological aspects, from "scientific evidence" contributed by systematic reviews to the way it can be obtained using handbooks and guidelines of inestimable value for the successful completion of our research. All such resources will help researchers to set out their hypotheses correctly, to test them adequately and to analyze the data in the most appropriate and rigorous fashion. In this way, the quality of the research will undoubtedly improve. © 2014 Asociación Española de Psicología Conductual.